From mass media to new media in contemporary Irish drama: Billy Roche's On Such As We and Paul Meade's Skin Deep - Patrick Lonergan (Ilha do Desterro)
This article explores the impact of new media and the mass media on the production, composition and reception of contemporary Irish drama. It considers the emergence of several tensions in that genre, notably that between mobility and stasis and the local and the global. This development is considered in relation to a discussion of two plays: Billy Roche's On Such As We, which was produced at the Peacock Theatre in 2001, and Paul Meade's Skin Deep, premiered by his company Gúna Nua at the Project Arts Centre in Dublin in 2003.